2010
DOI: 10.3390/su2123831
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Local Strawberry Rhizosphere—Associated Streptomycetes on the Bacterially—Induced Growth and Botrytis cinerea Infection Resistance of the Fruit

Abstract: Abstract:The future need for sustainable agriculture will be met in part by wider use of biological control of plant pathogens over conventional fungicides hazardous to the environment and to public health. Control strategies involving both (i) direct use of microorganisms antagonistic to the phytopathogen, and (ii) use of bioactive compounds (secondary metabolites/antibiotic compounds) from microorganisms on the phytopathogen were both adapted in order to investigate the ability of streptomycetes isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Streptomycetes sp. K2 was isolated from strawberry field soils, and promoted the growth of strawberry plants and fruits (Eccleston et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomycetes sp. K2 was isolated from strawberry field soils, and promoted the growth of strawberry plants and fruits (Eccleston et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Actinomycetes are one of the most efficient groups of natural bioactive metabolites, and they have been used as antibiotics, antitumor agents, antioxidants, anti-inflammatory agents, anti-infection agents, enzyme inhibitors, pesticides, plant-growth-promoting substances, and so on (Qin et al, 2011 ; Wang X. J. et al, 2013 ; Ashokvardhan et al, 2014 ; Kumar V. et al, 2014 ; Shivlata and Satyanarayana, 2015 ; Tan et al, 2016 ). It has been reported that actinomycetes have been used to protect plants against a wide range of phytopathogenic fungi, and produce cell-wall degrading enzymes, antifungal antibiotics, and plant growth promoters (Yuan and Crawford, 1995 ; El-Tarabily et al, 2000 ; Doumbou et al, 2002 ; Bressan, 2003 ; Cao et al, 2005 ; El-Tarabily and Sivasithamparam, 2006 ; Prapagdee et al, 2008 ; Jorjandi et al, 2009 ; Eccleston et al, 2010 ; Mingma et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although different groups of microorganisms have been employed for disease management, several research findings over the past few decades have highlighted the biocontrol potential of actinobacteria against a wide range of plant pathogens [ 19 , 20 , 21 ] through various mechanisms, including fungal cell-wall lysis, antibiosis, competition for nutrients, induction of host systemic resistance, phytotoxin degradation, plant growth stimulation, nutrient assimilation, rhizosphere competence and mineral availability [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%